Penerapan Model Problem Based Learning dengan Pendekatan Scientific untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Hunaidah .; Luh Sukariasih (Jurnal Aplikasi Fisika, 2016)
Has been conducting research with the title: "Application of Model Problem Based Learning Approach Scientific to Increase Activity and Learning Outcomes Grade VIIII SMP Negeri 5 Kendari Main Material Plane Simple (Class Action Research in Class VIIIi SMP Negeri 5 Kendari Semister I Academic Year 2014 / 2015) ". This research has been conducted in the first semester of the academic year 2014/2015, which took place on October 1 to October 7 2014 Junior High School 5 Kendari. Subjects in this study were students VIIIiSekolah SMP Negeri 5 Kendaripada semester of academic year 2014/2015 the number of students 35 people. The data obtained in this study is the activity and the thoroughness of learning outcomes derived from observations and test results sheet belajar.Analisis data were statistically deskriptif.Hasil of this research are: 1) the activity of students in the process pembelajan tends to increase, which is shown by the acquisition score on average in the first cycle of 2.45 included in the category enough and rose by 0.65 in the second cycle to 3.1 were categorized as good; 2) learning outcomes VIIIi grade science students SMP Negeri 5 Kendari taught with the application of Problem Based Learning with Scientific approach to the range of scores obtained as follows: the first cycle obtained a score of 1.4 up to 3.7 with an average score of 2, 84 and a standard deviation of 0.44; in the second cycle obtained a score of 2.00 up to 3.85 with an average score of 3.15 and a standard deviation of 0.37; and 3) learning outcomes VIIIi grade science students SMP Negeri 5 Kendari on the subject matter of simple air can be improved by applying the model of Problem Based Learning with Scientific approach, with the acquisition of an average score of student learning outcomes in the first cycle of 2.84 with the percentage of students who has been thoroughly studied by 71.43%, while in the second cycle of the average student learning outcomes increased to 3.15 with the percentage of students who have thoroughly studied by 91.43%